Burns education for non-burn specialist clinicians in Western Australia. Issue 2 (March 2015) - McWilliams, Tania; Hendricks, Joyce; Twigg, Di; Wood, Fiona
Highlights A state-wide learning needs assessment of non-burn specialist clinicians was conducted. Differences between perceived relevance and confidence in some areas of burn care demonstrated the need for further education and support. Data was used to develop a state-wide burns education programme delivered live to clinicians via videoconference. Significant improvement in non-burn specialist clinician knowledge was demonstrated following attendance for most education sessions. Videoconferencing is an acceptable and effective method of delivery for burns education.